The PIBID influences on the initial formation and teaching practice in basic education in the perception of its participants - Ramos, Rafael Nagy (2020)
This qualitative approach (BIKLEN; BOGDAN, 2013) study aims to evaluate the PIBID influences on the initial formation and teaching practice in basic education, regarding the UFMS presential degree courses, from 2009 to 2018. For the research, three stages were made that included: the bibliographic and exploratory phase, which consisted in the bibliographic review in national scientific production index basis and information survey about the program participants; the field collect phase, through online surveys with open and multiple-choice questions and; the third phase, in which the results statistical treatment about the respondent profiles and content analysis methodology use were made, in the Bardin´s (2016) perspective, for analyzing the information about the PIBID. The main identified categories regarding the program were: theoretical-practical relation; formation; opportunity; knowledge; importance; innovation and professional identity. The program, according to the respondents, provides teaching professional identity formation, higher information flow among the superior teaching institutions (IES) and the school, besides representing an academic growth opportunity. In conclusion, at the participants’ perception, the program is recognized as important, especially about its contributions for improving the initial formation, teaching identity construction, and teaching appreciation